The sedges and grasses of district Saharanpur (U.P.), India - Kumar, Ravinder; Saxena, R S (Current Botany, 2013)
The communication represents the study of sedges and grasses, which is the result of extensive survey and exploration of sedges and grasses of Saharanpur district form the period of January 2008 to December 2011. A total number of 110 species of Cyperaceae and Gramineae (Poaceae) have been collected from this area. Out of 110 species of these two families belonging to 64 genera, 77 species belong to Gramineae (Poaceae) and 33 species belong to Cyperaceae.